Evolutionary, comparative, and functional analyses of STATs and regulation of the JAK-STAT pathway in lumpfish upon bacterial and poly(I:C) exposure - Rao, Shreesha S.; Nelson, Patrick A.; Lunde, Harald S.; Haugland, Gyri T. (Frontiers in Cellular and Infection Microbiology, 2023)
The Janus kinase/signal transducers and activators of transcription (JAK-STAT) system regulates several biological processes by affecting transcription of genes as a response to cytokines and growth factors. In the present study, we have characterized the STAT genes in lumpfish (Cyclopterus lumpus L.), belonging to the order Perciformes, and investigated regulation of the JAK-STAT signaling pathway upon exposure to bacteria (Vibrio anguillarum) and poly(I:C), the latter mimicking antiviral responses.Methods: Characterization and evolutionary analyses of the STATs were performed by phylogeny, protein domain, homology similarity and synteny analyses. Antibacterial and antiviral responses were investigated by performing KEGG pathway analysis.We observed that lumpfish have stat1a, 2, 3, 4, 5a, 5b, and 6. Transcriptome-wide analyses showed that most components of the JAK-STAT pathway were present in lumpfish. il-6, il-10, il-21, iB and stat3 were upregulated 6 hours post exposure (hpe) against bacteria while type I interferons (IFNs), irf1, irf3, irf10, stat1 and 2 were upregulated 24 hpe against poly(I:C).Our findings shed light on the diversity and evolution of the STATs and the data show that the STAT genes are highly conserved among fish, including lumpfish. The transcriptome-wide analyses lay the groundwork for future research into the functional significance of these genes in regulating critical biological processes and make an important basis for development of prophylactic measure such as vaccination, which is highly needed for lumpfish since it is vulnerable for both bacterial and viral diseases.